2023
DOI: 10.1186/s12879-023-08154-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the human immunodeficiency virus of type 1 in Gabonese transfusional settings

Abstract: Background The high endemicity of transfusion-transmissible infections (TTIs) in sub-Saharan Africa is a real public health problem. To reduce the risk of HIV transmission through blood donation, the NBTC of Gabon has launched in recent years a reorganization of its blood transfusion system. This study aims to characterize the molecular strains of HIV-1 circulating in donors and to estimate the risk of viral transmission. Materials and methods A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“… 16 It is worth noting that despite the high burden of paediatric HIV-1 infection in SSA, there still persists a gap in data concerning the quantitative characterization of HIV-1 DNA in reservoirs, especially in the Central African sub-region which is known for its high genetic diversity of HIV-1. 17 , 18 Most of studies reporting data on the quantitative profile of HIV-1 reservoirs on the SSA paediatric populations were conducted in Southern African countries and were focusing on very early treated infants. 13 , 19 , 20 , 21 , 22 These studies have shown that higher CD4 + T cell percentage and lower pre-ART HIV-1 viral load are predictors of low levels of HIV-1 DNA 19 ; early ART initiation, longer ART duration as well as long-term virologic control reduce levels of HIV-1 DNA.…”
Section: Introductionmentioning
confidence: 99%
“… 16 It is worth noting that despite the high burden of paediatric HIV-1 infection in SSA, there still persists a gap in data concerning the quantitative characterization of HIV-1 DNA in reservoirs, especially in the Central African sub-region which is known for its high genetic diversity of HIV-1. 17 , 18 Most of studies reporting data on the quantitative profile of HIV-1 reservoirs on the SSA paediatric populations were conducted in Southern African countries and were focusing on very early treated infants. 13 , 19 , 20 , 21 , 22 These studies have shown that higher CD4 + T cell percentage and lower pre-ART HIV-1 viral load are predictors of low levels of HIV-1 DNA 19 ; early ART initiation, longer ART duration as well as long-term virologic control reduce levels of HIV-1 DNA.…”
Section: Introductionmentioning
confidence: 99%